Genetic Analysis Reveals A Missense Mutation In Reactivation Gene-2 Causing Severe Combined Immunodeficiency Disease In A Pakistani Family - Shahida Awais; Lubna Siddique; Nida Shafi; Sobia Humerah; Summyah Niazi; Wafa Omer (Journal of Rawalpindi Medical College)
Abstract